2019
DOI: 10.3390/foods9010023
|View full text |Cite
|
Sign up to set email alerts
|

Method of Food Preparation Influences Blood Glucose Response to a High-Carbohydrate Meal: A Randomised Cross-over Trial

Abstract: The aim of this study was to establish the blood glucose response to different cooking methods of pasta. Participants consumed three identical meals in a random order that were freshly cooked (hot), cooled and reheated. Blood glucose concentrations were assessed before, and every 15 min after ingestion of each meal for 120 min. There was a significant interaction between temperature and time (F ( 8.46 – 372.34 ) = 2.75, p = 0.005), with the reheated (90 min) condition returning to baseline faster t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
12
2
Order By: Relevance
“…Although the formation of retrograded starch upon cold storage has been widely reported, there are relatively few studies of re-heated retrograded starch, and current understanding of the starch structural changes and mechanisms that occur under re-heating conditions is limited. A recent human study reported a slightly lower area under postprandial glucose curves following ingestion of reheated pasta compared with freshly cooked pasta, 22 however contrary to what would be expected from the literature on cooling and resistant starch, 32,33 this study found no significant difference between hot and cold pasta. 22 Studies performed on other carbohydrate foods types suggest that refrigeration prior to re-heating reduces starch digestibility and in some case, glycaemic responses.…”
Section: Food and Function Papercontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the formation of retrograded starch upon cold storage has been widely reported, there are relatively few studies of re-heated retrograded starch, and current understanding of the starch structural changes and mechanisms that occur under re-heating conditions is limited. A recent human study reported a slightly lower area under postprandial glucose curves following ingestion of reheated pasta compared with freshly cooked pasta, 22 however contrary to what would be expected from the literature on cooling and resistant starch, 32,33 this study found no significant difference between hot and cold pasta. 22 Studies performed on other carbohydrate foods types suggest that refrigeration prior to re-heating reduces starch digestibility and in some case, glycaemic responses.…”
Section: Food and Function Papercontrasting
confidence: 99%
“…A recent human study reported a slightly lower area under postprandial glucose curves following ingestion of reheated pasta compared with freshly cooked pasta, 22 however contrary to what would be expected from the literature on cooling and resistant starch, 32,33 this study found no significant difference between hot and cold pasta. 22 Studies performed on other carbohydrate foods types suggest that refrigeration prior to re-heating reduces starch digestibility and in some case, glycaemic responses. For instance, in a study on parboiled rice, there was a tendency for glycaemic responses to be lower when boiled rice had been refrigerated prior to re-heating, however the difference in the postprandial glycaemic response between freshly cooked and re-heated rice was not statistically significant.…”
Section: Food and Function Papercontrasting
confidence: 99%
See 1 more Smart Citation
“…Consuming precooked potatoes, cold, has been shown to elicit a lower glycaemic response than the equivalent freshly cooked potatoes (Leeman et al 2005), whereas no differences were observed between freshly cooked and chilled-reheated boiled potatoes (Fernandes et al 2005). In contrast, a reduction in glycaemic response was observed following a reheated pasta meal in comparison with freshly cooked, with no differences observed for a chilled pasta meal (Hodges et al 2020). Similarly, chilled and reheated white rice elicited a lower glycaemic response than freshly cooked white rice (Sonia et al 2015).…”
Section: Effects Of Cooling and Reheating On Glycaemic Responsementioning
confidence: 92%
“…Nutritional science is rapidly growing and widening its horizon by taking into consideration the meal, the “event” of the meal (i.e., time-sequencing strategies and time-restricted feeding [ 3 ]), and the “process” through which the food undergoes, such as for packaged foods. Recently, the importance of food preparation has been pointed out by several observations describing the relevance of domestic attention to these issues to obtain benefits in terms of metabolic response [ 4 , 5 ]. Dietary carbohydrates are the main components of a balanced diet [ 1 ].…”
Section: Introductionmentioning
confidence: 99%